Effectiveness, safety and economic viability of daycare versus usual hospital care management of severe pneumonia with or without malnutrition in children using the existing health system of Bangladesh: a cluster randomised controlled trialResearch in context - Nur H. Alam; Abu S. Faruque; Hasan Ashraf; Mohammod J. Chisti; Tahmeed Ahmed; Marufa Sultana; Md Khalequzzaman; Shahjahan Ali; Shahnawaz Ahmed; Sabiha Nasrin; Md Tariqujjaman; K.A.T.M Ehsanul Haque; et al. (EClinicalMedicine, 2023)
Summary: Background: We aimed to define clinical and cost-effectiveness of a Day Care Approach (DCA) alternative to Usual Care (UC, comparison group) within the Bangladesh health system to manage severe childhood pneumonia. Methods: This was a cluster randomised controlled trial in urban Dhaka and rural Bangladesh between November 1, 2015 and March 23, 2019. Children aged 2–59 months with severe pneumonia with or without malnutrition received DCA or UC. The DCA treatment settings comprised of urban primary health care clinics run by NGO under Dhaka South City Corporation and in rural Union health and family welfare centres under the Ministry of Health and Family welfare Services. The UC treatment settings were hospitals in these respective areas. Primary outcome was treatment failure (persistence of pneumonia symptoms, referral or death). We performed both intention-to-treat and per-protocol analysis for treatment failure. Registered at www.ClinicalTrials.gov, NCT02669654. Findings: In total 3211 children were enrolled, 1739 in DCA and 1472 in UC; primary outcome data were available in 1682 and 1357 in DCA and UC, respectively. Treatment failure rate was 9.6% among children in DCA (167 of 1739) and 13.5% in the UC (198 of 1472) (group difference, −3.9 percentage point; 95% confidence interval (CI), −4.8 to −1.5, p = 0.165). Treatment success within the health care systems [DCA plus referral vs. UC plus referral, 1587/1739 (91.3%) vs. 1283/1472 (87.2%), group difference 4.1 percentage point, 95% CI, 3.7 to 4.1, p = 0.160)] was better in DCA. One child each in UC of both urban and rural sites died within day 6 after admission. Average cost of treatment per child was US$94.2 (95% CI, 92.2 to 96.3) and US$184.8 (95% CI, 178.6 to 190.9) for DCA and UC, respectively. Interpretation: In our population of children with severe pneumonia with or without malnutrition, >90% were successfully treated at Day care Clinics at 50% lower cost. A modest investment to upgrade Day care facilities may provide a cost-effective, accessible alternative to hospital management. Funding: UNICEF, Botnar Foundation, UBS Optimus Foundation, and EAGLE Foundation, Switzerland.